2022
DOI: 10.1039/d2ta02604j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the rigid and sterically bulky structure of non-fused nonfullerene acceptors on transient photon-to-current dynamics

Abstract: Non-fused electron-accepting π-conjugated compounds have been investigated recently for application to nonfullerene acceptors (NFAs) in organic solar cells (OSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…However, the present vertically separated CS geometries with (θ, ϕ) = (20, 0°) strongly denote that the phonon-assisted hole-dissociations occur only via the one-dimensional (1D) carrier-conductions 64 and should be a characteristic of the nonpolymer solar cells, as opposed to the three-dimensional (3D) routes for carrier dissociations found in polymer solar cells at cryogenic conditions. 28,31 This difference indicates that the present 1D carrier motions can readily cause recombination loss 64 from the highly separated e−h pairs via the assistance of phonons because backward e−h encounters are more plausible to occur than in the 3D environments. This well supports the time-resolved photocurrent observations that demonstrated the nanosecond carrier recombination dynamics by the first-and second-order processes.…”
Section: Connection Between Cell Performance and Microscopic Structurementioning
confidence: 92%
See 1 more Smart Citation
“…However, the present vertically separated CS geometries with (θ, ϕ) = (20, 0°) strongly denote that the phonon-assisted hole-dissociations occur only via the one-dimensional (1D) carrier-conductions 64 and should be a characteristic of the nonpolymer solar cells, as opposed to the three-dimensional (3D) routes for carrier dissociations found in polymer solar cells at cryogenic conditions. 28,31 This difference indicates that the present 1D carrier motions can readily cause recombination loss 64 from the highly separated e−h pairs via the assistance of phonons because backward e−h encounters are more plausible to occur than in the 3D environments. This well supports the time-resolved photocurrent observations that demonstrated the nanosecond carrier recombination dynamics by the first-and second-order processes.…”
Section: Connection Between Cell Performance and Microscopic Structurementioning
confidence: 92%
“…Although several methods have been applied to elucidate the elementary processes of charge carriers in BHJ-OSCs, mechanistic details of nonradiative loss in the open-circuit voltage ( V OC ) are poorly understood originating from interfacial heterogeneous electron–hole pairs. A recent time-resolved electron paramagnetic resonance (TREPR) study suggested an impact of the recombination process generating the triplet excitons in nonfullerene acceptor solar cells, while geometries and motions of charge-separated (CS) states were elucidated in details by electron spin polarization (ESP). Furthermore, although effects of low-frequency nuclear motions (phonon) on photocarrier generations have been discussed in several studies, , the microscopic role of the phonon on OPV performance is unclear, including the impact of the phonon assist on primary recombination processes. Here, we combine microscopic and spectroscopic methods to elucidate the origins of charge-generation and recombination in BHJ-OSC with C4-DPP-benzoporphyrin conjugates as the small-molecule donors.…”
Section: Introductionmentioning
confidence: 99%
“…2b). [32][33][34] As shown in Fig. 2c, density functional theory (DFT) calculations using model compounds indicate that both TT-FT-ID and TT-T-ID possess higher LUMO and HOMO energy levels than those of TT-FT-DCI.…”
Section: Introductionmentioning
confidence: 92%
“…Because of the aforementioned reasons, the CN stretching vibration is ideally suited to interrogating the dynamics of photoinduced charge transfer or separation via ultrafast optical-pump–IR-probe spectroscopic techniques. For example, it has been extensively used to investigate the dynamics of the locally excited (LE) and the intramolecular charge-transfer (ICT) states of 4-dimethylaminobenzonitrile (DMABN) (Figure , (5)), as well as other systems. More recently, the CN stretching vibration has also been used to assess various charge generation and separation steps in OPV devices, as demonstrated in several studies. , For A-D-A type of acceptors, an excited-state symmetry breaking (ES-SB) process, which leads the initially symmetrically distributed electronic excitation to become localized on one side (i.e., on one A) of the molecule, can occur under appropriate solvent conditions. , An example is the recent study of Vauthey and co-workers, who investigated the ES-SB properties of two A-D-A molecules (Figure , (6) and (7)), where D is a pyrrolo-pyrrole moiety and A is either a cyanophenyl or a dicyanovinyl group, using time-resolved vibrational spectroscopy. By comparing the transient absorption spectra of the CN group as well as other results obtained on these two systems, they concluded that although dicyanovinyl is a stronger EW moiety, ES-SB is not observed with the dicyanovinyl-based molecule even in highly polar media due to the large electronic coupling between the corresponding D and A branches.…”
Section: Application Of Cn Stretching Vibration In Energy Sciencementioning
confidence: 99%
“…80 fs. Likewise, Yutaka and co-workers took advantage of the sensitivity of the CN stretching vibration to the electron density around the nitrile triple bond and used it to study the photoexcited dynamics of two different OPV acceptors, TT-FT-DCI (Figure , (11)) and TT-T-DCI (Figure , (12)). Moreover, the CN stretching vibrational mode has been employed to assess the structure and dynamics of various energy-related molecules and systems via two-dimensional IR (2D IR) spectroscopy. …”
Section: Application Of Cn Stretching Vibration In Energy Sciencementioning
confidence: 99%